Result-based agri-environment measures: Market-based instruments, incentives or rewards? The case of Baden-Württemberg. (July 2016) - Russi, Daniela; Margue, Hélène; Oppermann, Rainer; Keenleyside, Clunie
Abstract: Result-based agri-environment measures are increasingly seen as an interesting way to improve the conditionality and efficiency of the use of Common Agricultural Policy (CAP) funding for environmental land management. They differ from classical action-based measures in that they remunerate farmers to achieve a desired outcome, and not for complying with a set of rules. We have analysed MEKA-B4, the result-based agrienvironment measure in place in Baden-Württemberg (Germany) between 2000 and 2014, which aimed to preserve species-rich grassland. In order to do so, we carried out semi-structured face-to-face interviews with participating and non-participating farmers and key institutional actors. We argue that MEKA-B4 could be considered a Payment for Ecosystem Services (PES), but only if a broad definition is adopted, as the payment appeared to cover the opportunity costs of only some categories of farmers (e.g., part-time farmers, less productive fields, hay producers), but it was too low to cover those of intensive cattle raisers and biogas producers, partly due to the changing market conditions (e.g., fluctuating and decreasing price of hay; incentives to produce biogas). In fact, in general most farmers were motivated to join the scheme by a combination of extrinsic motivations (i.e., the monetary incentive) and intrinsic motivations (i.e., ethical reasons). Increasing the payment, as has been done in the new version of the scheme (FAKT-B3), may help to ensure a wider enrolment in the measure in the long term. However, the interaction with biogas subsidies and other measures of the FAKT programme may hamper the farmers' enrolment. This shows the need to improve the integration and coherence of environmental policies that have different objectives.